transform do syntax to >>= with ((->) r) monad - haskell

On the page http://en.wikibooks.org/wiki/Haskell/do_Notation, there's a very handy way to transform the do syntax with binding to the functional form (I mean, using >>=). It works well for quite a few case, until I encountered a piece of code involving functions as monad ((->) r)
The code is
addStuff :: Int -> Int
addStuff = do
a <- (*2)
b <- (+10)
return (a+b)
this is equivalent as define
addStuff = \x -> x*2+(x+10)
Now if I use the handy way to rewrite the do part, I get
addStuff = (*2) >>= \a ->
(+10) >>= \b ->
a + b
which gives a compiling error. I understand that a, b are Int (or other types of Num), so the last function (\b -> a + b) has type Int -> Int, instead of Int -> Int -> Int.
But does this mean there's not always a way to transform from do to >>= ? Is there any fix to this? Or I'm just using the rule incorrectly?

Problem to make the last monadic:
addStuff = (*2) >>= \a ->
(+10) >>= \b ->
return (a + b)

(you've already been answered, that) The correct expression must use return on the last line:
addStuff = (*2) >>= \a ->
(+10) >>= \b ->
return (a + b)
(expounding on that, for some clarification) i.e. return is part of a monad definition, not of do notation.
Substituting the actual definitions for ((->) r) monad, it is equivalent to
addStuff x
= ((\a -> (\b -> return (a + b)) =<< (+10) ) =<< (*2) ) x
= (\a -> (\b -> return (a + b)) =<< (+10) ) (x*2) x
= ( (\b -> return ((x*2) + b)) =<< (+10) ) x
= (\b -> return ((x*2) + b)) (x+10) x
= return ((x*2) + (x+10)) x
= const ((x*2) + (x+10)) x
= (x*2) + (x+10)
as expected. So in general, for functions,
do { a <- f ; b <- g ; ... ; n <- h ; return r a b ... n }
is the same as
\ x -> let a = f x in let b = g x in ... let n = h x in r a b ... n
(except that each identifier a,b,...,n shouldn't appear in the corresponding function call, because let bindings are recursive, and do bindings aren't).
The above do code is also exactly how liftM2 is defined in Control.Monad:
> liftM2 (+) (*2) (+10) 100
310
liftM_N for any N can be coded with the use of liftM and ap:
> (\a b c -> a+b+c) `liftM` (*2) `ap` (+10) `ap` (+1000) $ 100
1410
liftM is the monadic equivalent of fmap, which for functions is (.), so
(+) `liftM` (*2) `ap` (+10) $ x
= (+) . (*2) `ap` (+10) $ x
= ((+) . (*2)) x ( (+10) x )
= (x*2) + (x+10)
because ap f g x = f x (g x) for functions (a.k.a. S-combinator).

Related

proving monad laws of a new monad instance (list of maybe)

I made a new List of Maybe Monad instance and tried to prove the implementation does satisfy the Monad laws, am I doing it right or is the implementation incorrect? Any pointer is appreciated. Thanks!
newtype Test a = Test { getTest :: [Maybe a] }
deriving Functor
instance Applicative Test where
pure = return
(<*>) = liftM2 ($)
instance Monad Test where
return :: a -> Test a
return a = Test $ [Just a]
(>>=) :: Test a -> (a -> Test b) -> Test b
Test [Nothing] >>= f = Test [Nothing]
Test [Just x] >>= f = f x
{-
1. return x >>= f = f x
return x >>= f = [Just x] >>= f = f x
2. m >>= return = m
[Nothing] >>= return = [Nothing]
[Just x] >>= return = return x = [Just x]
3. (m >>= f) >>= g == m >>= (\x -> (f x >>= g))
m = [Nothing]
L.H.S. = ([Nothing] >>= f ) >>= g = Nothing >>= g = Nothing
R.H.S. = [Nothing] >>= (\x -> (f x >>= g)) = Nothing
m = [Just x]
L.H.S. = ([Just x] >>= f) >>= g = f x >>= g
R.H.S. = [Just x] >>= (\v -> (f v >>= g)) = (\v -> (f v >>= g)) x
= f x >>= g
-}
The bits of the proof you have written are only incorrect in unimportant ways. Specifically, in these two lines:
([Nothing] >>= f ) >>= g = Nothing >>= g = Nothing
[Nothing] >>= (\x -> (f x >>= g)) = Nothing
The three bare Nothings should be [Nothing]s.
However, the proof is incomplete, because there are values of type Test a that are neither of the form [Just (x :: a)] nor [Nothing]. This makes the proof as a whole incorrect in an important way.

Understanding do notation for simple Reader monad: a <- (*2), b <- (+10), return (a+b)

instance Monad ((->) r) where
return x = \_ -> x
h >>= f = \w -> f (h w) w
import Control.Monad.Instances
addStuff :: Int -> Int
addStuff = do
a <- (*2)
b <- (+10)
return (a+b)
I'm trying to understand this monad by unwiding the do notation, because I think the do notation hides what happens.
If I understood correctly, this is what happens:
(*2) >>= (\a -> (+10) >>= (\b -> return (a+b)))
Now, if we take the rule for >>=, we must understand (*2) as h and (\a -> (+10) >>= (\b -> return (a+b))) as f. Applying h to w is easy, let's just say it is 2w (I don't know if 2w is valid in haskell but just for reasoning lets keep it this way. Now we have to apply f to h w or 2w. Well, f simply returns (+10) >>= (\b -> return (a+b)) for an specific a, which is 2w in our case, so f (hw) is (+10) >>= (\b -> return (2w+b)). We must first get what happens to (+10) >>= (\b -> return (2w + b)) before finally applying it to w.
Now we reidentify (+10) >>= (\b -> return (2w + b)) with our rule, so h is +10 and f is (\b -> return (2w + b)). Let's first do h w. We get w + 10. Now we need to apply f to h w. We get (return (2w + w + 10)).
So (return (2w + w + 10)) is what we need to apply to w in the first >>= that we were tyring to uwind. But I'm totally lost and I don't know what happened.
Am I thinking in the rigth way? This is so confusing. Is there a better way to think of it?
You're forgetting that operator >>= doesn't return just f (h w) w, but rather \w -> f (h w) w. That is, it returns a function, not a number.
By substituting it incorrectly you lost the outermost parameter w, so it's no wonder it remains free in your final expression.
To do this correctly, you have to substitute function bodies for their calls completely, without dropping stuff.
If you substitute the outermost >>=, you will get:
(*2) >>= (\a -> ...)
==
\w -> (\a -> ...) (w*2) w
Then, if you substitute the innermost >>=, you get:
\a -> (+10) >>= (\b -> return (a+b))
==
\a -> \w1 -> (\b -> return (a+b)) (w1 + 10) w1
Note that I use w1 instead of w. This is to avoid name collisions later on when I combine the substitutions, because these two ws come from two different lambda abstractions, so they're different variables.
Finally, substitute the return:
return (a+b)
==
\_ -> a+b
Now insert this last substitution into the previous one:
\a -> (+10) >>= (\b -> return (a+b))
==
\a -> \w1 -> (\b -> return (a+b)) (w1 + 10) w1
==
\a -> \w1 -> (\b -> \_ -> a+b) (w1 + 10) w1
And finally insert this into the very first substitution:
(*2) >>= (\a -> ...)
==
\w -> (\a -> ...) (w*2) w
==
\w -> (\a -> \w1 -> (\b -> \_ -> a+b) (w1 + 10) w1) (w*2) w
And now that all substitutions are compete, we can reduce. Start with applying the innermost lambda \b -> ...:
\w -> (\a -> \w1 -> (\_ -> a+w1+10) w1) (w*2) w
Now apply the new innermost lambda \_ -> ...:
\w -> (\a -> \w1 -> a+w1+10) (w*2) w
Now apply \a -> ...:
\w -> (\w1 -> w*2+w1+10) w
And finally apply the only remaining lambda \w1 -> ...:
\w -> w*2+w+10
And voila! The whole function reduces to \w -> (w*2) + (w+10), completely as expected.
First, we write out the implicit argument in your definition explicitly,
addStuff :: Int -> Int
addStuff = do
a <- (*2)
b <- (+10)
return (a+b)
=
addStuff :: Int -> Int
addStuff x = ( do
a <- (*2)
b <- (+10)
return (a+b) ) x
=
....
Then, with
return x = const x
(f =<< h) w = f (h w) w -- (f =<< h) = (h >>= f)
it should be easier to follow and substitute the definitions, line for line:
....
=
( (*2) >>= (\a -> -- (h >>= f) =
(+10) >>= (\b ->
const (a+b) ) ) ) x
=
( (\a -> -- = (f =<< h)
(+10) >>= (\b ->
const (a+b) ) ) =<< (*2) ) x -- (f =<< h) w =
=
(\a ->
(+10) >>= (\b ->
const (a+b) ) ) ( (*2) x) x -- = f (h w) w
=
( let a = (*2) x in -- parameter binding
(+10) >>= (\b ->
const (a+b) ) ) x
=
let a = (*2) x in -- float the let
((\b ->
const (a+b) ) =<< (+10) ) x -- swap the >>=
=
let a = (*2) x in
(\b -> -- (f =<< h) w =
const (a+b) ) ( (+10) x) x -- = f (h w) w
=
let a = (*2) x in
(let b = (+10) x in -- application
const (a+b) ) x
=
let a = (*2) x in -- do a <- (*2)
let b = (+10) x in -- b <- (+10)
const (a+b) x -- return (a+b)
The essence of reader monad is application to same argument shared between all calls.
Intuitively, each function call on the right-hand side of the <- is given an additional argument, which you can think of as the argument to addStuff itself.
Take
addStuff :: Int -> Int
addStuff = do
a <- (*2)
b <- (+10)
return (a+b)
and turn it into
addStuff :: Int -> Int
addStuff x = let a = (*2) x
b = (+10) x
in (a+b)
It looks a little less "strange" if you use the MonadReader instance for (->) r, which provides ask as a way to get direct access to the implicit value.
import Control.Monad.Reader
addStuff :: Int -> Int
addStuff = do
x <- ask -- ask is literally just id in this case
let a = x * 2
let b = x + 10
return (a + b)

How binding works in function monads in Haskell?

From learn you a haskell: http://learnyouahaskell.com/for-a-few-monads-more
Monad instance for function is this:
instance Monad ((->) r) where
return x = \_ -> x
h >>= f = \w -> f (h w) w
I am having trouble understanding the output of the following:
import Control.Monad.Instances
addStuff :: Int -> Int
addStuff = do
a <- (*2)
b <- (+10)
return (a+b)
addStuff 3 returns 19. Book says 3 gets passed as parameters to both (*2) and (+10). How?
From h >>= f = \w -> f (h w) w , it seems like (h w) is getting bound to a or b.
So, why 6 is not being passed in (+10)?
My understanding of f here is that when (*2) is h, f is the last 2 lines of addStuff. When (+10) is h, f is the last line (in this case the return statement) of addStuff.
Let us first desugar the do block [Haskell'10 report]:
addStuff = do
a <- (*2)
b <- (+10)
return (a+b)
is equivalent to:
addStuff = (*2) >>= \a -> ((+10) >>= \b -> return (a + b))
The inner bind expression ((+10) >>= \b -> return (a + b)), can thus be converted, with the bind definition to:
\w -> (\b -> return (a + b)) ((+10) w) w
and if we substitute return with const, we thus obtain:
\w -> (const . (a+)) ((+10) w) w
We thus have a function that takes as input w, and then calls const . (a+) on (w+10) and w, so it will ignore the last w. Semantically it is equivalent to:
(a+) . (+10)
So now our addStuf is equivalent to:
addStuff = (*2) >>= \a -> ((a+) . (+10))
and if we now use the definition for the bind operator again, we see:
\w -> (\a -> ((a+) . (+10))) ((*2) w) w
or shorter:
\w -> (\a -> ((a+) . (+10))) (w*2) w
We can now substitue a with (w*2) and obtain:
\w -> ((w*2)+) . (+10)) w
So our addStuf is equivalent to:
addStuff w = (w*2) + (w+10)
or more simple:
addStuff w = 3*w + 10
Haskell do notation is syntactic sugar for a series of >>= bindings; in this case, for something like this:
addStuff = (*2) >>= (\a -> (+10) >>= (\b -> return (a + b)))
Passing the updated argument between the computation steps (which would thus be serving a role of a state) is the job of another monad, namely the State monad.
The function aka Reader monad is simpler than that, does less work:
-- (return x) w = x
-- (h >>= f) w = f (h w) w
(h >>= (\a -> g >>= (\b -> return (f a b)))) w
=
(\a -> g >>= (\b -> return (f a b))) (h w) w
=
(g >>= (\b -> return (f (h w) b))) w
=
(\b -> return (f (h w) b))) (g w) w
=
return (f (h w) (g w)) w
=
f (h w) (g w)
Thus the input argument w is passed unchanged into both (by extension, all) the computation steps. Or in the specific case you ask about,
liftM2 (+) ( *2) ( +10) w
=
(+) (w*2) (w+10)
liftM2 function is equivalent to the do block that you show,
liftM2 f h g =
do {
a <- h ;
b <- g ;
return (f a b) }
=
h >>= (\ a ->
g >>= (\ b -> return (f a b) ))
in any monad.

How to rewrite in point-free style with a repeating variable?

How to rewrite the following expression in point-free style?
p x y = x*x + y
Using the lambda-calculus I did the following:
p = \x -> \y -> (+) ((*) x x) y
= \x -> (+) ((*) x x) -- here start my problem
= \x -> ((+) . ((*) x )) x
... ?
I asked lambdabot
<Iceland_jack> #pl p x y = x*x + y
<lambdabot> p = (+) . join (*)
join is from Control.Monad and normally has this type
join :: Monad m => m (m a) -> m a
but using instance Monad ((->) x) (if we could left section types this could be written (x ->)) we get the following type / definition
join :: (x -> x -> a) -> (x -> a)
join f x = f x x
Let's ask GHCi to confirm the type:
>> import Control.Monad
>> :set -XTypeApplications
>> :t join #((->) _)
join #((->) _) :: (x -> x -> a) -> x -> a
Since you mentioned Lambda Calculus I will suggest how to solve this with SK combinators. η-reduction was a good try, but as you can tell you can't η-reduce when the variable is used twice.
S = λfgx.fx(gx)
K = λxy.x
The feature of duplication is encoded by S. You simplified your problem to:
λx.(+)((*)xx)
So let us start there. Any lambda term can be algorithmically transformed to a SK term.
T[λx.(+)((*)xx)]
= S(T[λx.(+)])(T[λx.(*)xx]) -- rule 6
= S(K(T[(+)]))(T[λx.(*)xx]) -- rule 3
= S(K(+))(T[λx.(*)xx]) -- rule 1
= S(K(+))(S(T[λx.(*)x])(T[λx.x])) -- rule 6
= S(K(+))(S(*)(T[λx.x])) -- η-reduce
= S(K(+))(S(*)I) -- rule 4
In Haskell, S = (<*>) and K = pure and I = id. Therefore:
= (<*>)(pure(+))((<*>)(*)id)
And rewriting:
= pure (+) <*> ((*) <*> id)
Then we can apply other definitions we know:
= fmap (+) ((*) <*> id) -- pure f <*> x = fmap f x
= fmap (+) (join (*)) -- (<*> id) = join for Monad ((->)a)
= (+) . join (*) -- fmap = (.) for Functor ((->)a)
If you go to http://pointfree.io/
For
p x y = x*x + y
It gives you
p = (+) . join (*)
Just for fun, you can use the State monad to write
p = (+) . uncurry (*) . runState get
runState get simply produces a pair (x, x) from an initial x; get copies the state to the result, and runState returns both the state and that result.
uncurry (*) takes a pair of values rather than 2 separate values ((uncurry (*)) (3, 3) == (*) 3 3 == 9).

Converting `do` Notation `addStuff` to `>>=`

Learn You a Haskell presents the addStuff function:
import Control.Monad.Instances
addStuff :: Int -> Int
addStuff = do
a <- (*2) -- binds (*2) to a
b <- (+10) -- binds (+10) to b
return (a+b) -- return has type sig: 'Monad m => a -> m a'
Are the types of a, b, and return (a+b) all Int -> Int? I think so, but I'm not sure how bind-ing plays a role.
I tried to implement it using >>=, but I'm not sure how to complete it (hence ...).
addStuff' :: Int -> Int
addStuff' = (*2) >>= (+10) >>= ...
Please give me a hint to complete it, as well as edit my understanding of the do notation version.
As I understand, the ... needs to include a type of Int -> Int. In the do version, I could use a and b, but I'm not sure how to add them with the >>= version.
When working with the reader monad (a.k.a. the function monad), you have the type a -> b, which can be rewritten as (->) a b. The actual monad instance here is
instance Monad ((->) r) where
return x = const x
f >>= g = \r -> g (f r) r
Notice that during >>=, the type is
(>>=) :: ((->) r a) -> (a -> ((->) r b)) -> ((->) r b)
Which can be rewritten as
(>>=) :: (r -> a) -> (a -> (r -> b)) -> (r -> b)
Or even
(>>=) :: (r -> a) -> (a -> r -> b) -> (r -> b)
So as you can see, what >>= does is take a single input, apply that to f, and then apply that result to g to produce a new function r -> b. So for your example, you could use:
addStuff' :: Int -> Int
addStuff' = (*2) >>= (+)
And so addStuff' 10 == 30, since it performs the computation (10 * 2) + (10). Note how 10 is fed both to (*2) and (+), and the result of (10*2) is fed to (+) as well. It might make things a little more clear to see it as
test :: Int -> (Int, Int, Int)
test = do
x <- (*2)
y <- (*3)
z <- (*5)
return (x, y, z)
And it's result would be
> test 1
(2, 3, 5)
> test 10
(20, 30, 50)
What this essentially is doing is taking the argument to test "before" it's been applied, feeding it to each of the functions on the right hand side of the <-s, and then combining that result in the return.
So how can you write these without do notation? You could do something like
test :: Int -> (Int, Int, Int)
test =
(\r -> r * 2) >>= (\x ->
(\r -> r * 3) >>= (\y ->
(\r -> r * 5) >>= (\z ->
return (x, y, z))))
Which, admittedly, is not very readable, even with formatting, but the gist is basically that r gets fed to each intermediate function, which produces a result, and a couple nested lambda expressions later you return all three of those results in a tuple.
With a bit of simplification, you could also make each of those nested lambdas into two arguments lambdas:
test =
(\r -> r * 2) >>=
(\x r -> r * 3) >>=
(\y r -> r * 5) >>=
(\z r -> const (x, y, z) r)
I've also replaced the last \z -> return (x, y, z) with its equivalent \z -> const (x, y, z) => \z r -> const (x, y, z) r, just so they all have the same form.
As a rough rule if you want to manually desugar do-notation, first erase the do at the top and flip the bind arrow (<-) on the left-hand-side to a (>>=) on the right-hand-side with the variable on the left as a lambda variable on the right. So:
addStuff :: Int -> Int
addStuff = do
a <- (*2)
... rest ...
Becomes:
addStuff :: Int -> Int
addStuff =
(*2) >>= (\a ->
... rest ...
)
This is recursive, so the next term in the do-notation then becomes nested in the lambda of the desugared term above it, all the way down to the last expression which is just the body of the nested lambda expression.
The desugaring is quite mechanical, it's defined by the following rewrites, where ; denotes a newline.
do { a <- f ; m } ≡ f >>= \a -> do { m }
do { f ; m } ≡ f >> do { m }
do { m } ≡ m
Both a and b are of type Int while return (a+b) has type Int -> Int which is the last term in the do-notation so it has to be identical to the toplevel signature. Using -XScopedTypeVariables we can manually annotate the subterms:
{-# LANGUAGE ScopedTypeVariables #-}
import Control.Monad.Instances
addStuff :: Int -> Int
addStuff = do
(a :: Int) <- (*2)
(b :: Int) <- (+10)
(return (a+b)) :: Int -> Int
Thanks to bheklilr.
I wrote my own code.
addStuff :: Int -> Int
addStuff = (\r -> r * 2) >>= (\x ->
(\r -> r + 10) >>= (\y ->
return (x + y)))

Resources